2019
DOI: 10.3168/jds.2019-16396
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and nutrient digestibility of lactating dairy cows fed low-forage diets with and without the addition of a live-yeast supplement

Abstract: We aimed to evaluate the use of a live-yeast product as a means to attenuate plausible nutritional disturbances when feeding relatively low-forage diets containing rapidly fermentable carbohydrates (i.e., wheat) to high-producing cows in early to mid lactation. Eight primiparous [mean ± SD; 569 ± 35 kg of body weight (BW) and 80 ± 29 d in milk (DIM) at the beginning of the experiment] and 16 multiparous (665 ± 67 kg of BW and 64 ± 10 DIM at the beginning of the experiment) Holstein cows were blocked by parity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Dietary treatments did not affect BW or BCS in the current study (Table 2), which agrees with previous studies with live yeast (Ambriz-Vilchis et al, 2017;Ferreira et al, 2019) and yeast culture (Dias et al, 2018b). Yeast supplementation effects on BCS and BW are seldomly reported in adult dairy cows and seem to have a more consistent effect when supplemented to young ruminants (Alugongo et al, 2017).…”
Section: Effects On Dmi Bw Bcs and Ebsupporting
confidence: 92%
“…Dietary treatments did not affect BW or BCS in the current study (Table 2), which agrees with previous studies with live yeast (Ambriz-Vilchis et al, 2017;Ferreira et al, 2019) and yeast culture (Dias et al, 2018b). Yeast supplementation effects on BCS and BW are seldomly reported in adult dairy cows and seem to have a more consistent effect when supplemented to young ruminants (Alugongo et al, 2017).…”
Section: Effects On Dmi Bw Bcs and Ebsupporting
confidence: 92%
“…Bitencourt et al [31] reported that dietary NDF digestibility increased by 11.3% with the use of 10 10 cfu/day of LY and milk yield increased by 0.9 kg/day, which supports the proposition in the previous sentence. However, Ferreira et al [32] reported no significant difference in milk yield in lactating dairy cows due to yeast use. Moreover, the addition of 60 g yeast/ day to the diet of Holstein dairy cows for 84 days in midlactation during a period of heat stress did not enhance milk production or affect its components [8].…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, Ferreira et al (2019) evaluated the use of a live-yeast product when feeding relatively low-forage diets containing rapidly fermentable carbohydrates to high-producing cows and found no differences in production performance or nutrient utilization. Based on the low NDF digestibility coefficients, the authors suggested that conditions for fiber digestion may not have been optimal and that the potential benefit of supplementing the live-yeast product may have been hindered by the rapid rate of passage of fiber particles attributed to the low concentration of forage NDF (14.3% forage NDF), the low proportion of forage in the diet (~45% forage), or their combination.…”
Section: Short Communicationmentioning
confidence: 99%
“…Two nonpelleted concentrates (control and yeast) were prepared at a commercial feed mill (Big Spring Mill Inc., Elliston, VA). The live-yeast product (BeneSacc; Global Nutritech Biotechnology, LLC, Richmond, VA), which contained 4.5 × 10 −9 cfu/g of Saccharomyces cerevisiae, was delivered through a premix that was prepared onfarm by mixing 7.5 kg of live-yeast product with 625 kg of soybean meal (Ferreira et al, 2019). The resulting premix was bagged and submitted to the feed mill, where it was included in the nonpelleted concentrate to provide 12 g of product for every 24 kg of DM.…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation